2019
DOI: 10.3390/ma12142248
|View full text |Cite
|
Sign up to set email alerts
|

Novel Synthesis of Holey Reduced Graphene Oxide/Polystyrene (HRGO/PS) Nanocomposites by Microwave Irradiation as Anodes for High-Temperature Lithium-Ion Batteries

Abstract: To overcome the risk of exothermic lithium-ion battery overheating reactions, we fabricated a novel, high-temperature-stable anode material composed of holey reduced graphene oxide/polystyrene (HRGO/PS) nanocomposites synthesized through in situ bulk polymerization in the presence of HRGO via microwave irradiation. The HRGO/PS nanocomposites were characterized by Fourier transform infrared spectroscopy, X-ray diffraction, Raman spectroscopy, and electron microscopy analyses including field-emission scanning el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…In situ bulk synthesis of holey reduced graphene oxide/ polystyrene (HRGO/PS) nanocomposites with 0.1%, 1%, and 2% HRGO concentrations via in situ polymerization was conducted using microwave irradiation by Aldawsari et al 77 A mixture of styrene, HRGO, and benzoyl peroxide was sonicated for 1 h, maintained at 60 1C for 20 h to promote polymerization, sonicated for an additional 1 h, then reduced by microwave irradiation. Electrical conductivity studies were conducted on neat PS and HRGO/PS, and showed that neat PS was insulative with an electrical conductivity in the range of 10 À2 -10 À7 S cm À1 .…”
Section: Pccp Reviewmentioning
confidence: 99%
“…In situ bulk synthesis of holey reduced graphene oxide/ polystyrene (HRGO/PS) nanocomposites with 0.1%, 1%, and 2% HRGO concentrations via in situ polymerization was conducted using microwave irradiation by Aldawsari et al 77 A mixture of styrene, HRGO, and benzoyl peroxide was sonicated for 1 h, maintained at 60 1C for 20 h to promote polymerization, sonicated for an additional 1 h, then reduced by microwave irradiation. Electrical conductivity studies were conducted on neat PS and HRGO/PS, and showed that neat PS was insulative with an electrical conductivity in the range of 10 À2 -10 À7 S cm À1 .…”
Section: Pccp Reviewmentioning
confidence: 99%
“…Solvents usually need to be microwave absorbing and thermally conductive materials. [27][28][29][30][31] For the last decade, solvent-free microwave irradiation synthesis methods have been gradually developed [32][33][34][35][36][37][38] and some novel uses of solvent-free microwave irradiation have been explored such as microwave carbonization 39 and the synthesis of nanoparticles. 36 Previous studies showed that graphene can effectively absorb microwaves and generate a lot of heat and the temperature can rapidly rise above 1000 C in a few seconds, and the particles loaded on the graphene can transform into nanoparticles from microparticles.…”
Section: Introductionmentioning
confidence: 99%